Input parameter extraction method for point scatterer formulation in vegetation media at millimetre-wave frequencies - Leonor, Nuno R. (2018)
An empirical method to extract the relevant point scatterer formulation input parameters for appropriate radio coverage simulation in vegetation areas, is proposed. While the original propagation model would require the prior knowledge of the complete tree(s) re-radiation function(s) to extract the relevant propagation input parameters, the empirical method proposed herein is based only on two simple measurements. Re-radiation measurements of several specimens of Thuja pelicata and Ficus benjamina trees at two frequencies have been used to validate the proposed simplified extraction method. The proposed empirical model was then used to characterise the propagation phenomena of various trees arranged in four different scenarios. Subsequently, directional spectra measurements performed inside an anechoic chamber at both 20 and 62.4 GHz were used to assess the empirical model performance, while predicting the received signal level arriving from various directions. A relatively good overall model performance when applied to tree formations was obtained which, coupled with the simplified parameter extraction proposed, makes it suitable to be integrated in commercial simulation platforms and/or as input data to other propagation models that may require the prior knowledge of the individual tree re-radiation functions.